Influence of School Library on Implementing Qualitative Science Education in Nigeria: Impediments and the Possibilities - Olajide, Olabode; Oyeniran, Kayode Gboyega; Anyakorah, Ozimede Zuwelatu; Omolehin, Rotimi James; Lucas-Elumah, Busayo Abidemi (Communicate: Journal of Library and Information Science, 2023)
This study investigated the influence of school libraries on implementing qualitative science education in Nigeria: impediments and the possibilities. The methodological approach adopted for this study was mixed methods. The study’s population was 1,152, which comprised library staff, principals, and science teachers in public senior secondary schools as well as major stakeholders in education connected with the provision, management and utilization of library resources for teaching science subjects. The instruments of data collection were questionnaires, interviews, and observation. Quantitative data were analysed using the SPSS, while qualitative data were transcribed and analysed thematically. The findings show that the state of school libraries was poor and the resource most frequently available in school libraries for teaching science was textbooks, and many of the library staff did not possess a librarianship qualification. Findings also showlibrary resources (textbooks) as being influential in science curriculum implementation, and the majority of teachers adopted a teacher-centred approach.